ACCOUNTABILITY OF VILLAGE FUND ALLOCATION POLICIES ( STUDY: IN GALUNG VILLAGE, BARRU DISTRICT, BARRU DISTRICT ) - Lukman, Sri Hardiyanti; Musdalifa; Suriani (Meraja journal, 2023)
[Full Paper] to pdf Copyright (c) 2023 Meraja journal